Mediating role of academic attitude on sports participation and academic performance - Alahmed, Mustafa; Yusof, Aminuddin; M. Shah, Parilah (AkiNik Publications, 2016)
This study examines the mediating effect of academic attitude on the relationship between sport participation and academic achievement of student athletes in Saudi Arabia. A total of 102 subjects comprising of undergraduate student athletes from Saudi Arabia were randomly selected as the sample of this study. Participation in competitive sport is measured as frequency of the students’ participation in sports activities in a week (Wicker, Hallmann, Breuer, 2013) and whether the students are active members of sport university teams (Lindner & Kerr, 2000) or sport clubs (Dollman& Lewis, 2010). Academic achievement is measured by the formal academic report from the student athletes’ respective university. Survey of Study Habits & Attitudes (SSHA) by Brown and Holtzman (1956) was adapted to measure academic attitude. Result indicates a positive significant relationship between participation in competitive sport and academic achievement. Results also showed a partial mediation of academic attitude on the relationship between sport participation and academic achievement. It was concluded that when a student athlete developed a positive attitude towards academic achievements, the level of their participation in the sport competition will positively affect their academic scores.